2007
DOI: 10.1519/r-20245.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Maximal Cardiorespiratory Performance and Muscle Power in the Italian Olympic Judoka

Abstract: The main purposes of this study were to describe the cardiorespiratory fitness and lower limbs maximal muscle power of a selected group of Olympic Italian male (M) and female (F) judokas. Eleven subjects (6 M, 5 F) underwent 3 different tests. The VO(2)max and ventilatory threshold (VT; V-slope method) were assessed during a graded maximal treadmill test. Lower limbs muscle peak power (PP) and mean power (MP) were determined during a 30-second Wingate test (WIN). Post-WIN blood lactate peak was also measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 15 publications
3
43
3
Order By: Relevance
“…2005). Sbriccoli et al, (2007) were identified that the muscle power was at a high level and the aerobic capacities were quite good on the Italian olympic judokas. (Sbriccoli et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…2005). Sbriccoli et al, (2007) were identified that the muscle power was at a high level and the aerobic capacities were quite good on the Italian olympic judokas. (Sbriccoli et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…An established measure of anaerobic power is the Wingate Anaerobic Test (WAnT; 7, 13) and despite some limitations (8), it is widely used for athletic populations (25,27). WAnT presents additional appeals to the assessment of water polo players.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiation of functional fitness estimates of highly skilled combat athletes of different weight categories on the basis of developed model characteristics allows more accurate characterization of their physical state and functional reserves, manifested in the responses to physical load at various stages of annual preparation cycle in different ways. Besides, it also permits to concretize physical state monitoring and management of lightweights and heavyweights fitness according to the major indices of cardiac activity, gas analysis and special work capacity, which is absolutely new as compared to the findings of other researchers (Pankov, 2002;Pilianidis et al, 2011;Sbricolli et al, 2007).…”
Section: Jpes ®mentioning
confidence: 96%
“…Employment of the methods of complex and systemic analysis, multivariate statistics has allowed to develop adequate mathematical models and to use them for modelling physical state of wrestlers and elaborating differentiated system of estimates of the level of FF and special work capacity according to various key informative and integral indices. It has become an absolutely new approach in the system of biological monitoring of physical state of wrestlers, which is absent in similar studies of other researchers (Iushkov, 2002;Pankov, 2002;Erkan, 2011;Pilianidis et al, 2011;Sbricolli, Bazzucchi, Mario, Marzattinocci, & Felici, 2007). Differentiation of functional fitness estimates of highly skilled combat athletes of different weight categories on the basis of developed model characteristics allows more accurate characterization of their physical state and functional reserves, manifested in the responses to physical load at various stages of annual preparation cycle in different ways.…”
Section: Jpes ®mentioning
confidence: 99%